Ameliorating English speaking skill: students’ voice on the use of byTALK application - Maryam Asyafina (Erudita: Journal of English Language Teaching, 2025)
Speaking is a crucial skill in English learning but many students still struggle due to limited practice, low confidence, and lack of feedback. While various mobile applications support language learning, few offer real-time speaking practice, leaving a gap in tools that fully develop speaking competence. This study aimed to explore students’ voices on the use of the byTALK application to ameliorate their English-speaking skills. A qualitative approach was employed through the use of narrative inquiry, involving four English Education students from a university in Pekalongan, Indonesia. Data were garnered through self-reflection and semi-structured interviews, and analyzed using Appraisal Theory, focusing on the Affect subsystem to examine emotional responses. The findings revealed both positive and negative voices. Students expressed happiness, motivation, and confidence as they improved in comprehension, grammar, vocabulary, pronunciation, and fluency. However, they also experienced frustration, insecurity, and dissatisfaction due to limited internet access, absence of grammar and pronunciation support, and peer distractions. These findings highlight how byTALK fosters both linguistic growth and emotional engagement. This study suggests that byTALK can serve as an effective tool to support speaking skill development and promote learner autonomy in mobile assisted language learning contexts.